FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAYARAN DIVIDEN - VASHTI INES; IRWANTO HANDOJO (Jurnal Bisnis dan Akuntansi, 2017)
This research aims to identify variables that influence dividend policy in manufacturing public companies. These variables are profitability, firm size, liquidity, growth opportunities, leverage, firm risk, individual ownership and institutional ownership. This research was also to compare with result of previous research. Samples of this research are listed manufacturing companies in Indonesia Stock Exchange from 2011 until 2013. Samples were collected using purposive sampling method, where 37 companies fulfill the established criteria. This research uses multiple regression to test the hypothesis. The result from this study shows that profitability and institutional ownership influence to dividend policy, but firm size, liquidity, growth opportunities, leverage, firm risk, and individual ownership do not influence toward dividend policy.